Rambutan-like porous carbon, preparation method, electrode and testing method thereof
Rambutan-like porous carbon is prepared by double-salt melt activation method, which solves the problems of low electrochemical utilization rate and high safety risks in the preparation process of existing porous carbon materials, and realizes the preparation of materials with high specific surface area and excellent electrochemical energy storage characteristics, and is simple in the process and environmentally friendly.
Patent Information
- Application Number
- CN202510016245.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-11
AI Technical Summary
In the electrochemical energy storage applications, existing porous carbon materials have problems such as low electrochemical utilization, high safety risks in preparation process, high cost and complex process.
Rambutan-like porous carbon was prepared by double-salt melt activation method. By uniformly mixing the asphalt coke after fine sieves with Na2CO3 and K2CO3 activators, and the activation reaction was carried out under a nitrogen atmosphere. Then, the HCl solution and deionized water were used for cleaning and drying, a rambutan-like porous carbon rich in micropores and mesoporous was obtained.
Rambutan-like porous carbon with high specific surface area and two-dimensional morphology has achieved excellent electrochemical energy storage characteristics, and is simple in process and environmentally friendly, suitable for industrial scale production.
Smart Images

Figure CN119811903A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of porous materials and electrochemical energy storage, and provides a rambutan-like porous carbon, a preparation method, an electrode and a testing method thereof. Background Art
[0002] As a power device, supercapacitors have the characteristics of high safety, long cycle life, and fast charge and discharge speed. They are widely used in national defense security, military equipment, power peak regulation, rail transportation, logistics elevators and other fields to meet the needs of short-term high-frequency use. Supercapacitors are composed of electrode materials, current collectors, diaphragms and electrolytes. Among them, electrode materials, as an important part of energy storage devices, determine the energy storage materials of supercapacitors. Porous carbon materials have the characteristics of high specific surface area and high conductivity, and are ideal electrode materials for supercapacitors. Traditional porous carbon materials are prepared by KOH activation and have rich pore structures. However, the electrochemical utilization rate of the materials is low, and there is a safety risk of "alkali explosion" during the preparation process. Graphene two-dimensional materials have large specific surface area and theoretical specific capacity, but they have disadvantages such as low tap density, complex preparation process and high cost, which limit their application in high volume capacity supercapacitors. In recent years, flower-shaped porous carbon has attracted widespread attention. Nanoflowers assembled from two-dimensional sheets have large surface area, high electrical conductivity and high tap density, and can be used as carriers to prepare high-capacity electrode materials. It is a feasible solution to improve the energy density of supercapacitors. CN118116749A discloses a method for preparing asphalt-based porous carbon nanosheets suitable for zinc ion supercapacitors, using asphalt as a raw material, urea, melamine and 3,5-diamino-1,2,4-triazole as nitrogen sources for mixing, introducing a photoinitiator to initiate polymerization by ultraviolet irradiation, and then carbonizing and activating at high temperature in nitrogen to obtain a porous carbon material. However, the calcination temperature of this method is high and the steps are complicated, and it is necessary to initiate polymerization by ultraviolet light to obtain a porous carbon material. CN106348290A discloses a preparation of a high thermal conductivity asphalt-based spherical activated carbon, which is obtained by mixing high softening point asphalt, naphthalene and a thermal conductor to obtain a modified asphalt, and using physical activation to activate the asphalt spherical activated carbon product. The asphalt spherical activated carbon obtained by this method has a low specific surface area and the modifier pollutes the environment and is harmful to the human body, so it is not conducive to industrial-scale production. Summary of the invention
[0003] The invention provides a method for preparing rambutan-like porous carbon. The rambutan-like porous carbon has the advantages of high specific surface area and two-dimensional morphology and exhibits excellent electrochemical energy storage characteristics.
[0004] The technical solution is as follows:
[0005] A method for preparing rambutan-like porous carbon, the method adopts double salt melting activation to prepare rambutan-like porous carbon; the method is characterized by comprising the following steps:
[0006] Step 1: crushing the asphalt coke by using a jet mill, and then grading and screening to obtain finely screened asphalt coke;
[0007] Step 2: uniformly mixing the finely screened asphalt coke with Na2CO3 and K2CO3 activators according to a mass ratio to obtain a mixed material;
[0008] Step 3: placing the mixed material in a tubular furnace under a nitrogen atmosphere, heating it to a certain temperature at a certain heating rate and keeping it for several hours to perform an activation reaction, then cooling it to room temperature and taking it out;
[0009] Step 4: heating and stirring the activated material with HCl solution and deionized water, and washing until the solution is neutral;
[0010] Step 5: Filter and dry the product obtained in step 4 to obtain the rambutan-like porous carbon.
[0011] Preferably, the particle size of the pitch coke after fine screening in step 1 is 2-15 microns. Screening the pitch coke within this particle size range allows it to be fully mixed with the Na2CO3 and K2CO3 activators, and it is easier to control the particle size of the activated porous carbon after the activation reaction. In addition, too large a particle size of the porous carbon has a great influence on the capacitance performance of the material. Controlling the particle size of the porous carbon to 7-10 microns can maximize the capacitance performance of the material.
[0012] Preferably: the mass ratio of asphalt coke to Na2CO3, K2CO3 activator after fine screening in step 2 is 1:1-1:4, wherein the molar ratio of Na2CO3 and K2CO3 is 0:1-1:0. Composite carbonate (Na2CO3, K2CO3) as an activator can greatly reduce the melting point of the activator, so that the activator melts at a lower temperature, and the molten liquid activator contacts the solid asphalt coke more fully, and the reaction rate of the solid-liquid reactor formed is faster. The single carbonate activator has a high melting point (Na2CO3851℃, K2CO3891℃), and the decomposition rate is slow, which is not conducive to the preparation of rambutan-like porous carbon. Carbonate decomposes when reaching its melting point, and the decomposition product is alkali metal oxide and CO2, and alkali metal oxide has certain catalytic and reduction characteristics, can catalyze the formation of rambutan-like porous carbon, and can also reduce carbon-containing gas (CO, CO2) to achieve carbon fixation effect. By selecting different molar ratios of Na2CO3 and K2CO3, the formation temperature and time of the molten salt activator can be designed. The preferred molar ratio of Na2CO3 and K2CO3 is 0.555:0.445, and the prepared rambutan-like porous carbon channel structure and graphene-like nanosheet growth are optimal.
[0013] Preferably, step 3 further comprises: the activation temperature is 800°C-1000°C (preferably 950°C), the activation reaction time is 5h, and the heating rate is 5°C / min. The activation temperature controls the morphological growth and pore development of the porous carbon material. When the activation temperature is lower than 800°C, the decomposition of the activator is insufficient and the pore structure cannot be fully developed. When the activation temperature is higher than 1000°C, the porous carbon microstructure guided by high temperature undergoes an irreversible graphitization transformation, and this more ordered graphite microstructure is not conducive to capacitor energy storage.
[0014] Preferably, in step 4, the concentration of hydrochloric acid is 2 mol / L, and the stirring time is 5-8 hours. The purity of the porous carbon material has a great influence on the performance of the material. The activated product of the double salt melt activation reaction contains a large amount of Na2CO3 and K2CO3. The use of a higher concentration of hydrochloric acid to pickle the activated product can clean the remaining activator and other impurities in the product, ensuring that the rambutan-like porous carbon exerts the best capacitance performance.
[0015] Preferably, the product obtained in step 5 is placed in a 120°C oven for drying for 12-24 hours. The moisture content also has a great influence on the capacitance performance of the porous carbon material, and a high moisture content is not conducive to electrode preparation. After filtration, a lot of moisture is adsorbed on the surface of the rambutan-like porous carbon material, and the moisture contained in the material can be removed by drying in a 120°C environment.
[0016] The invention discloses an electrode, which is characterized in that the rambutan-like porous carbon is prepared by double salt melting activation.
[0017] The present invention adopts a test method for testing the electrochemical performance of electrodes, which is a test method for testing the above-mentioned electrodes; the electrode electrochemical performance test is carried out using a three-electrode system, using a 6M KOH solution as an electrolyte, a platinum sheet electrode as a counter electrode, and a mercuric oxide electrode as a reference electrode. Supercapacitor energy storage is carried out through surface electrochemical physical adsorption / desorption. The three-electrode system can be used to test the electrochemical performance of a single electrode material in a 6M KOH electrolyte. + and OH- ion adsorption and desorption properties.
[0018] The invention also discloses a rambutan-like porous carbon, which is characterized in that the rambutan-like porous carbon is prepared by adopting the above method.
[0019] Preferably, the rambutan-like porous carbon comprises a large number of micropores and mesopores, the micropore diameter is distributed in the range of 0.55 nm, and the mesopore diameter is distributed in the range of 2.64 nm; -1 At a current density of 1.34 W / m, the discharge capacity in aqueous alkaline electrolyte is 163 F g -1 The rambutan-like porous carbon includes a large number of micropores and mesoporous structures, which can provide a higher specific surface area and provide more adsorption / desorption sites during the capacitive energy storage process.
[0020] The core of the present invention is step 2 and step 3. Through the design of the activator and the control of the activation temperature, a porous carbon rich in micropores and mesopores, rambutan-like, is prepared. A mixed salt of Na2CO3 and K2CO3 is used as a template and an activator. By designing the ratio of the two in the mixed salt of Na2CO3 and K2CO3, Na2CO3 and K2CO3 form a molten state at a minimum of 710°C. The Na ions and K ions in the liquid phase are in full contact with the asphalt coke, cutting off the longer fat bond side chains in the asphalt coke and guiding the long chains to recombine. At the same time, the gas generated by the decomposition of Na2CO3 and K2CO3 leads to the generation of more pores, and finally forms a porous carbon rich in micropores and mesopores, rambutan-like, through polycondensation and gas diffusion.
[0021] Beneficial Effects
[0022] 1. Using pitch coke as raw material, a simple, environmentally friendly and green method was adopted to prepare rambutan-like porous carbon.
[0023] 2. The present invention uses asphalt coke as a raw material, and adopts Na2CO3 and K2CO3 mixed salt as a template and activator. At a relatively low temperature, Na2CO3 and K2CO3 form a molten state, and Na ions and K ions in the liquid phase fully contact the asphalt coke, cut off the longer fat bond side chains in the asphalt coke, guide the long chains to reorganize, and finally form graphene-like carbon sheets through polycondensation. The molten liquid phase activator not only promotes the migration rate of Na / K ions and increases the activation contact area, but also acts as a template, forming a porous structure and also causing a graphene-like sheet structure grown on the surface, forming a rambutan-like porous carbon.
[0024] 3. The rambutan-like porous carbon has a special two-dimensional morphology and a hierarchical porous structure. The high ductility of its two-dimensional surface is conducive to the storage and surface adsorption and desorption of electrolyte ions. The present invention can obtain a rambutan-like porous carbon with a high specific surface area and rich pore structure at a relatively low activation temperature, which can be used as a supercapacitor electrode material with very good capacitance performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a scanning electron microscope image of the rambutan-like porous carbon prepared in Example 1.
[0026] Figure 2 This is a transmission electron microscopy image of the rambutan-like porous carbon prepared in Example 1.
[0027] Figure 3 This is the electrochemical performance diagram of the rambutan-like porous carbon prepared in Example 1.
[0028] Figure 4 This is the isothermal adsorption diagram of the rambutan-like porous carbon prepared in Example 1.
[0029] Figure 5 This is the pore size distribution diagram of the rambutan-like porous carbon prepared in Example 1. DETAILED DESCRIPTION
[0030] The embodiments of the present invention will be described in detail below in conjunction with examples, but those skilled in the art will understand that the following examples are only used for the present invention and should not be regarded as limiting the scope of the present invention. The present invention will be further described below in conjunction with the accompanying drawings and examples.
[0031] A method for preparing rambutan-like porous carbon, the method adopts double salt melting activation to prepare rambutan-like porous carbon; the method is characterized by comprising the following steps:
[0032] Step 1: crushing the asphalt coke by using a jet mill, and then grading and screening to obtain finely screened asphalt coke;
[0033] Step 2: uniformly mixing the finely screened asphalt coke with Na2CO3 and K2CO3 activators according to a mass ratio to obtain a mixed material;
[0034] Step 3: placing the mixed material in a tubular furnace under a nitrogen atmosphere, heating the material to a certain temperature at a certain heating rate and keeping the temperature for several hours to perform an activation reaction, then cooling the material to room temperature and taking it out;
[0035] Step 4: heating and stirring the activated material with HCl solution and deionized water, and washing until the solution is neutral;
[0036] Step 5: Filter and dry the product obtained in step 4 to obtain the rambutan-like porous carbon.
[0037] Example 1
[0038] A method for preparing rambutan-like porous carbon comprises the following steps:
[0039] (1) Weigh 100 g of asphalt coke and place it in a jet mill. The sample after jet milling is sieved to obtain finely sieved asphalt coke, wherein the particle size is 2-15 μm.
[0040] (2) The finely sieved asphalt coke is uniformly mixed with a mixed activator of Na2CO3 and K2CO3 in a mass ratio of 1:4, wherein the mass ratio of Na2CO3 to K2CO3 is 2:2, 10 g of the finely sieved asphalt coke is taken, and 20 g of Na2CO3 and K2CO3 are taken respectively to obtain a mixed material.
[0041] (3) The mixed material was placed in a tubular furnace in a nitrogen atmosphere for activation at an activation temperature of 950°C for 5 h with a heating rate of 5°C / min. After activation, the mixed material was naturally cooled to room temperature.
[0042] (4) The activated material was washed with 2 mol / L HCl solution and deionized water until the solution became neutral. Finally, it was placed in a freeze dryer for freeze drying for 12 h to obtain rambutan-like porous carbon.
[0043] (5) Preparation of electrodes: The prepared rambutan-like porous carbon, acetylene black, and binder polytetrafluoroethylene were mixed in a mass ratio of 80:10:10, deionized water was added to the mixture, and then pressed into a sheet and extruded onto the nickel foam, and dried in a vacuum drying oven at 120°C overnight.
[0044] (6) The electrochemical performance test of the obtained electrode was carried out using a three-electrode system, with 6M KOH solution as the electrolyte, platinum sheet as the counter electrode, and mercuric oxide electrode as the reference electrode. The cyclic voltammetry test, impedance test, and constant current charge and discharge performance test were performed using a Chenhua electrochemical workstation. The cyclic voltammetry test was set up with a voltage range of -1V to 0V and a scan rate of 10mV s-1 ; Impedance test setting, frequency range is 100KHz-0.01Hz, voltage is initial voltage; Constant current charge and discharge performance test setting, voltage range is -1V to 0V, current density is 1A -1 .
[0045] The rambutan-like porous carbon material obtained in Example 1 is shown in the accompanying drawings, wherein: Figure 1 The scanning electron microscope after activation shows that the prepared material is a rambutan-like porous carbon material with a two-dimensional flaky surface.
[0046] Figure 2 This is the transmission electron microscope image after activation. It can be clearly seen that the prepared material is a rambutan-like nanosheet ball.
[0047] Figure 3 The three-electrode constant current charge-discharge curve of the prepared rambutan-like porous carbon is shown in Figure 2. -1 At a current density of 1.5 %, it exhibits a high discharge capacity of 163 F g -1 .
[0048] Figure 4 The isothermal adsorption curve of the prepared rambutan-like porous carbon is shown in Figure 2. The isothermal adsorption-desorption test results show that the specific surface area of the material is 1210 m 2 g -1 From the figure, we can see that the sample has a type IV isotherm curve, indicating that the sample has a large number of micropores and a small amount of mesopores, proving that the material is a hierarchical porous structure.
[0049] Figure 5 The pore size distribution diagram of the prepared rambutan-like porous carbon is shown. The pore size distribution results show that the micropore size of the material is mainly distributed at 0.55 nm, while the mesopore size is 2.64 nm.
[0050] Example 2
[0051] (1) Weigh 100 g of asphalt coke and place it in a jet mill. The sample after jet milling is sieved to obtain finely sieved asphalt coke, wherein the particle size is 2-15 μm.
[0052] (2) The finely sieved asphalt coke is uniformly mixed with a mixed activator of Na2CO3 and K2CO3 in a mass ratio of 1:4, wherein the mass ratio of Na2CO3 to K2CO3 is 2:2, 10 g of the finely sieved asphalt coke is taken, and 20 g of Na2CO3 and K2CO3 are taken respectively.
[0053] (3) The mixed material was placed in a tubular furnace in a nitrogen atmosphere for activation at an activation temperature of 850°C for 5 h with a heating rate of 5°C / min. After activation, the mixed material was naturally cooled to room temperature.
[0054] (4) The activated material was washed with 2 mol / L HCl solution and deionized water until the solution became neutral. Finally, it was placed in a freeze dryer for freeze drying for 12 h to obtain rambutan-like porous carbon.
[0055] The rambutan-like porous carbon obtained through the above-mentioned embodiment is analyzed and found to have the following: the activation temperature is too low, which is not conducive to the development of pores and the specific surface area is small.
[0056] Example 3
[0057] (1) Weigh 100 g of asphalt coke and place it in a jet mill. The sample after jet milling is sieved to obtain finely sieved asphalt coke, wherein the particle size is 2-15 μm.
[0058] (2) The finely sieved asphalt coke is uniformly mixed with a mixed activator of Na2CO3 and K2CO3 in a mass ratio of 1:4, wherein the mass ratio of Na2CO3 to K2CO3 is 2:2, 10 g of the finely sieved asphalt coke is taken, and 20 g of Na2CO3 and K2CO3 are taken respectively.
[0059] (3) The mixed material was placed in a tubular furnace in a nitrogen atmosphere for activation at an activation temperature of 1000°C for 5 h with a heating rate of 5°C / min. After activation, the mixed material was naturally cooled to room temperature.
[0060] (4) The activated material was washed with 2 mol / L HCl solution and deionized water until the solution became neutral. Finally, it was placed in a freeze dryer for freeze drying for 12 h to obtain rambutan-like porous carbon.
[0061] The analysis of the rambutan-like porous carbon obtained in the above-mentioned embodiment shows that: the activation temperature is too high, and the two-dimensional morphology of the surface partially collapses, which is not conducive to the utilization of carbon materials.
[0062] Example 4
[0063] (1) Weigh 100 g of asphalt coke and place it in a jet mill. The sample after jet milling is sieved to obtain finely sieved asphalt coke, wherein the particle size is 2-15 μm.
[0064] (2) The finely sieved asphalt coke is uniformly mixed with a Na2CO3 mixed activator in a mass ratio of 1:4, wherein the mass ratio of Na2CO3 to K2CO3 is 4:0, 10 g of the finely sieved asphalt coke and 40 g of Na2CO3 are taken.
[0065] (3) The mixed material was placed in a tubular furnace in a nitrogen atmosphere for activation at an activation temperature of 1000°C for 5 h with a heating rate of 5°C / min. After activation, the mixed material was naturally cooled to room temperature.
[0066] (4) The activated material was washed with 2 mol / L HCl solution and deionized water until the solution became neutral. Finally, it was placed in a freeze dryer for freeze drying for 12 h to obtain rambutan-like porous carbon.
[0067] Through analysis of the rambutan-like porous carbon obtained in the above-mentioned embodiment, it can be seen that: when activated by sodium carbonate alone, although the specific surface area is high, the tap density is small and a two-dimensional morphology cannot be grown on the surface.
[0068] Example 5
[0069] (1) Weigh 100 g of asphalt coke and place it in a jet mill. The sample after jet milling is sieved to obtain finely sieved asphalt coke with a particle size of 2-15 μm.
[0070] (2) The finely sieved asphalt coke and K2CO3 mixed activator are uniformly mixed in a mass ratio of 1:4, wherein the mass ratio of Na2CO3 to K2CO3 is 0:4, 10 g of the finely sieved asphalt coke and 40 g of K2CO3 are taken.
[0071] (3) The mixed material was placed in a tubular furnace in a nitrogen atmosphere for activation at an activation temperature of 1000°C for 5 h with a heating rate of 5°C / min. After activation, the mixed material was naturally cooled to room temperature.
[0072] (4) The activated material was washed with 2 mol / L HCl solution and deionized water until the solution became neutral. Finally, it was placed in a freeze dryer for freeze drying for 12 h to obtain rambutan-like porous carbon.
[0073] The rambutan-like porous carbon obtained through the above-mentioned embodiment is analyzed and found to have a small specific surface area and poor capacitance performance when activated by potassium carbonate alone.
[0074] The rambutan-like porous carbon obtained in Examples 1-5 was tested, and the specific data are shown in Table 1:
[0075] Table 1
[0076]
[0077] As can be seen from Table 1, the method for preparing rambutan-like porous carbon by double salt melting provided by the present invention can obtain rambutan-like porous carbon with special morphology and high specific surface area. The rambutan-like porous carbon obtained by the scheme of Example 1 has a higher specific surface area and a larger tap density, and has better capacitance performance as a supercapacitor carbon.
[0078] The above is a detailed introduction to a rambutan-like porous carbon and a preparation method thereof provided by the present invention. The present invention introduces the synergistic effect of double salt melting. On the one hand, the template effect of sodium carbonate is used to inhibit the strong chemical reaction between potassium carbonate and the carbon-containing precursor. On the other hand, the introduction of potassium carbonate can make sodium carbonate melt with it, weakening the sodium carbonate template while promoting the growth of micropores. At the same time, a two-dimensional sheet structure grows on the surface. The two-dimensional sheet structure forms a surface conductive grid, which enhances the surface material activity, thereby achieving the effect of improving the tap density and conductivity, and maintaining a high specific surface area.
[0079] The above contents are only for the purpose of illustrating and describing the technical ideas and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited by the above embodiments, and the above embodiments and the specification only describe the technical ideas of the present invention. The present invention may have various changes and improvements without departing from the spirit and scope of the present invention, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing rambutan-like porous carbon, wherein the method adopts double salt melt activation to prepare rambutan-like porous carbon, and the method is characterized in that: The steps include: Step 1: crushing the asphalt coke by using a jet mill, and then grading and screening to obtain finely screened asphalt coke; Step 2: uniformly mixing the finely screened asphalt coke with Na2CO3 and K2CO3 activators according to a mass ratio to obtain a mixed material; Step 3: placing the mixed material in a tubular furnace under a nitrogen atmosphere, heating the material to a certain temperature at a certain heating rate and keeping the temperature for several hours to perform an activation reaction, then cooling the material to room temperature and taking it out; Step 4: heating and stirring the activated material with HCl solution and deionized water, and washing until the solution is neutral; Step 5: Filter and dry the product obtained in step 4 to obtain the rambutan-like porous carbon.
2. The method for preparing rambutan-like porous carbon according to claim 1, characterized in that: The particle size of the asphalt coke after air flow milling is 2-15 microns.
3. The method for preparing rambutan-like porous carbon according to claim 1, characterized in that: The step 2 further comprises: the mass ratio of the finely screened asphalt coke to the Na2CO3 and K2CO3 activators is 1:1-1:4, wherein the molar ratio of Na2CO3 to K2CO3 is 0:1-1:
0.
4. The method for preparing rambutan-like porous carbon according to claim 1, characterized in that: In step 3, the activation temperature is 800-1000° C., the activation reaction time is 2-5 h, the heating rate is 5° C. / min, and the activation reaction is naturally cooled to room temperature after completion.
5. The method for preparing rambutan-like porous carbon according to claim 1, characterized in that: In step 4, the concentration of hydrochloric acid is 2 mol / L, and the stirring time is 4-8 hours.
6. The method for preparing rambutan-like porous carbon according to claim 1, characterized in that: The product obtained in step 5 is placed in an oven and dried for 12-24 hours.
7. A rambutan-like porous carbon, characterized in that: The rambutan-like porous carbon is prepared by the method for preparing the rambutan-like porous carbon according to any one of claims 1 to 6.
8. The rambutan-like porous carbon according to claim 7, characterized in that: The rambutan-like porous carbon includes a large number of micropores and mesopores, has a two-dimensional morphology and a hierarchical porous structure, and the high ductility of its two-dimensional surface is conducive to the storage and surface adsorption and desorption of electrolyte ions; the micropore diameter distribution is 0.55nm, and the mesopore diameter is 2.64nm; at a current of 1A -1 At a current density of 1.34 W / m, the discharge capacity in aqueous alkaline electrolyte is 163 F g -1 .
9. An electrode; characterized by: The rambutan-like porous carbon described in claim 7 is mixed with acetylene black and polytetrafluoroethylene binder in a mass ratio of 8:1:1, deionized water is added dropwise, the mixture is pressed into a sheet, extruded onto nickel foam, and dried overnight in a vacuum drying oven at 120°C.
10. A test method for testing the electrochemical performance of an electrode, the test method is a test method for testing the electrode described in claim 9; the electrode electrochemical performance test is carried out using a three-electrode system, using a 6M KOH solution as an electrolyte, a platinum sheet electrode as a counter electrode, and a mercuric oxide electrode as a reference electrode.
Citation Information
Patent Citations
Preparing method of pitch-based spherical activated carbon with high heat conductivity
CN106348290A
Preparation method and application of asphalt-based porous carbon nanosheet suitable for zinc ion capacitor
CN118116749A